Redundancy allocation problem of a system with increasing failure rates of components based on Weibull distribution: A simulation-based optimization approach. (August 2016) - Guilani, Pedram Pourkarim; Azimi, Parham; Niaki, S.T.A.; Niaki, Seyed Armin Akhavan
Abstract: The redundancy allocation problem (RAP) is a useful method to enhance system reliability. In most works involving RAP, failure rates of the system components are assumed to follow either exponential or k-Erlang distributions. In real world problems however, many systems have components with increasing failure rates. This indicates that as time passes by, the failure rates of the system components increase in comparison to their initial failure rates. In this paper, the redundancy allocation problem of a series–parallel system with components having an increasing failure rate based on Weibull distribution is investigated. An optimization method via simulation is proposed for modeling and a genetic algorithm is developed to solve the problem. Graphical abstract: Highlights: The redundancy allocation problem of a series–parallel system is aimed. Components possess an increasing failure rate based on Weibull distribution. An optimization method via simulation is proposed for modeling. A genetic algorithm is developed to solve the problem.